Planned delivery for term infants (การคลอดที่มีการวางแผน) - Puapornpong, Pawin (Journal of Medicine and Health Sciences, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE TH MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Angsana New"; panose-1:2 2 6 3 5 4 5 2 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:16777219 0 0 0 65537 0; @font-face font-family:"Cordia New"; panose-1:2 11 3 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:16777219 0 0 0 65537 0; @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:14.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Angsana New"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-bidi-font-family:"Angsana New"; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Planned delivery is the delivery through is planned delivery route when term gestational age is completed. Gestational age can be confirmed by urine pregnancy test detection, crown-lump length measurement from ultrasonography and fetal heart detection from stethoscope or doptone. Choosing delivery route is based on the decision of patients, their family and obstetrician with consideration of patient data and risk factors. If patient can be liable to deliver by vaginal route, labor induction will be set up. The repeated cesarean section cases, mother with risk factors for cesarean section and cases with cesarean section on maternal request can choosing cesarean section route. However, cesarean section on maternal request with no medical indication has to be considered with high cautiousness.